(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper describes the design of a radio frequency identification system that we called Trees RFID Tracking System (TRTS). This suggested study develops a system that would enable the detection and identification of trees illegal logging cases and hence preventing risks of species distinction and deforestation threats. The TRTS consists of RFID passive tags (static tags) fitted in trees and serving as unique identity for each tree; handheld readers (moving devices) with a suitable readable range and embedded circular polarization antenna. These readers would be held by forest officers and the data read from the tags would be accessible through the readers thanks to a visualization software that would analyze and process the data received. The database that saves all the readings and user interface and enables access to that data is located at the server side of the system. Communication between the tag readers and the server side is done through 3G connectivity enabled at the handheld reader device. An example of this suggested study practicality is the forests in Ifrane region of Atlas Mountains which are well known for the cedar species that are constantly subject to illegal extracting and thus are threatened by extinction. Moreover there has been no suggested method to improve their management process. Here is where our RFID system comes to play